2022
DOI: 10.20525/ijrbs.v11i2.1643
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organizational politics on the individual work performance

Abstract: The study aimed to examine the effect of organizational politics on the individual work performance of employees. To support the study, literature was reviewed and theories were identified and explained. It was carried out following research methodology in terms of research design, population, the locale of the study, research instruments, and statistical treatment of data. The study found that the organizational politics of the institution is at a moderate level and the individual work performance was also at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In essence, the provision of job resources should correlate with the job demands situation (Nuutinen et al, 2022). In this case, resources would serve as a reward system to prompt employees to be committed to their job and the organization because they would realize that the organization cares (Abun et al, 2022). Hence, the focus of this article is on the assessment of supervisors to determine if they have the welfare of employees at heart through their provision of job resources.…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…In essence, the provision of job resources should correlate with the job demands situation (Nuutinen et al, 2022). In this case, resources would serve as a reward system to prompt employees to be committed to their job and the organization because they would realize that the organization cares (Abun et al, 2022). Hence, the focus of this article is on the assessment of supervisors to determine if they have the welfare of employees at heart through their provision of job resources.…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…Despite varying perspectives and dimensions regarding political behavior, studies and research indicate that desirable and effective political behavior in organizations is essential to enhance human and organizational productivity, and is now discussed as managing political behavior in organizational behavior trends. However, political behavior, like other aspects of organizational dynamics, is not a simple process and varies from one organization to another (Abun et al, 2022;Meydan & Köksal, 2019). The more an organizational culture emphasizes a win-lose approach, the greater the motivation of employees for political behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by data on employee turnover, which increases yearly. Several studies have proven that the work environment affects employee performance (Tleuken et al, 2022;Goet, 2022;Abun, 2022;Ibrahim et al, 2022;Ahakwa et al, 2021;Tasman et al, 2021;Badrianto & Ekhsan, 2020;Widyastuti et al, 2021;Na-Nan et al, 2019;Hafeez et al, 2019;Diamantidis & Chatzoglou, 2018;Hidayati et al, 2019;Solegar et al, 2018;Ikechukwu et al, 2019;Nzewi et al, 2017;and Siddiqi & Tangem, 2018). At the same time, several studies have shown that the work environment does not affect employee performance (Suparman Dadang, 2020; Riyadi, 2019;and Ahmad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%